2021
DOI: 10.3390/ijms22115556
|View full text |Cite
|
Sign up to set email alerts
|

DyP-Type Peroxidases: Recent Advances and Perspectives

Abstract: In this review, we chart the major milestones in the research progress on the DyP-type peroxidase family over the past decade. Though mainly distributed among bacteria and fungi, this family actually exhibits more widespread diversity. Advanced tertiary structural analyses have revealed common and different features among members of this family. Notably, the catalytic cycle for the peroxidase activity of DyP-type peroxidases appears to be different from that of other ubiquitous heme peroxidases. DyP-type perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 91 publications
3
73
0
Order By: Relevance
“…This class also contains peroxidases known to be involved in lignin degradation in Basidiomycota such as LiP, MnP, and VP [4][5][6]. Other fungal heme peroxidases such as DyP-type peroxidases were also implicated in lignin degradation, although a possibly related function has not yet been finally clarified [61]. The peroxidases identified from the C. aquatica genome, however, are more similar to the Ascomycota class II family [62].…”
Section: Discussionmentioning
confidence: 99%
“…This class also contains peroxidases known to be involved in lignin degradation in Basidiomycota such as LiP, MnP, and VP [4][5][6]. Other fungal heme peroxidases such as DyP-type peroxidases were also implicated in lignin degradation, although a possibly related function has not yet been finally clarified [61]. The peroxidases identified from the C. aquatica genome, however, are more similar to the Ascomycota class II family [62].…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes known as dye-decolorizing peroxidases (DyPs) also utilize protein radicals for substrate reactions. 84 Although the natural substrates are difficult to identify, DyPs can oxidize high potential substrates and are of interest for their role in lignin degradation. Both bacterial and fungal enzymes contain much higher levels of Trp and Tyr in their amino acid sequences than LP and VP.…”
Section: Functional Hole Hopping Through Metalloenzymesmentioning
confidence: 99%
“…Reactive Blue 5 and Reactive Blue 19 are typical structures of anthraquinone dye sand. BAD DyP can degrade Reactive Blue 5 by cleaving an anthraquinone framework [56,57]. A unique hydrolase mechanism has been proposed, which uses H 2 O released by peroxidase function to exert hydrolase activity during the degradation of anthrone (Figure 5A) [58].…”
Section: Dye Decolorizationmentioning
confidence: 99%
“…The construction of a gene database and phylogenetic analysis revealed the omics relationship between DyPs, and gene functions have been elucidated. It indicated that the research on DyPs could reach a new stage using molecular biology [57,63]. DyPs can maintain a high activity in acidic conditions and tend to express high activity at an acidic pH to degrade lignin substrates.…”
Section: Improvement Of Dyps Properties By Gene-editing Technologymentioning
confidence: 99%